Understanding employees' adoption of the Bring-Your-Own-Device (BYOD): the roles of information security-related conflict and fatigue. Issue 3 (6th June 2020) - Chen, Hao; Li, Ying; Chen, Lirong; Yin, Jin
Abstract : Purpose: While the bring-your-own-device (BYOD) trend provides benefits for employees, it also poses security risks to organizations. This study explores whether and how employees decide to adopt BYOD practices when they encounter information security–related conflict. Design/methodology/approach: Using survey data from 235 employees of Chinese enterprises and applying partial least squares based structural equation modeling (PLS-SEM), we test a series of hypotheses. Findings: The results suggest that information security–related conflict elicits information security fatigue among employees. As their information security fatigue increases, employees become less likely to adopt BYOD practices. In addition, information security–related conflict has an indirect effect on employee's BYOD adoption through the full mediation of information security fatigue. Practical implications: This study provides practical implications to adopt BYOD in the workplace through conflict management measures and emotion management strategies. Conflict management measures focused on the reducing of four facets of information security–related conflict, such as improve organization's privacy policies and help employees to build security habits. Emotion management strategies highlighted the solutions to reduce fatigue through easing conflict, such as involving employees in the development or update of information security policies to voice their demands of privacy and other rights. Originality/value: Our study extends knowledge by focusing on the barriers to employees' BYOD adoption when considering information security in the workplace. Specifically, this study takes a conflict perspective and builds a multi-faceted construct of information security–related conflict. Our study also extends information security behavior research by revealing an emotion-based mediation effect, that of information security fatigue, to explore the mechanism underlying the influence of information security–related conflict on employee behavior.